2013
DOI: 10.1371/journal.pone.0083563
|View full text |Cite|
|
Sign up to set email alerts
|

Matrix Metalloproteinase-3 in Odontoblastic Cells Derived from Ips Cells: Unique Proliferation Response as Odontoblastic Cells Derived from ES Cells

Abstract: We previously reported that matrix metalloproteinase (MMP)-3 accelerates wound healing following dental pulp injury. In addition, we reported that a proinflammatory cytokine mixture (tumor necrosis factor-α, interleukin (IL)-1β and interferon-γ) induced MMP-3 activity in odontoblast-like cells derived from mouse embryonic stem (ES) cells, suggesting that MMP-3 plays a potential unique physiological role in wound healing and regeneration of dental pulp in odontoblast-like cells. In this study, we tested the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…Conversely, the control siRNA had no such effect ( Figure 5A). Silencing the MMP-3 gene also significantly decreased IL-1β-stimulated cell proliferation (p < 0.01; Figure 5A) as described previously (9,10). Taken together, these data suggest that IL-1β-induced DMP-1 expression depends on the expression of MMP-3 in odontoblast-like cells.…”
Section: Effect Of Anti-mmp-3 Sirna On Il-1β-induced Dmp-1 Expressionsupporting
confidence: 86%
See 2 more Smart Citations
“…Conversely, the control siRNA had no such effect ( Figure 5A). Silencing the MMP-3 gene also significantly decreased IL-1β-stimulated cell proliferation (p < 0.01; Figure 5A) as described previously (9,10). Taken together, these data suggest that IL-1β-induced DMP-1 expression depends on the expression of MMP-3 in odontoblast-like cells.…”
Section: Effect Of Anti-mmp-3 Sirna On Il-1β-induced Dmp-1 Expressionsupporting
confidence: 86%
“…Notably, treatment with IL-1β induces potent expression of MMP-3 in dental pulp, a tissue that contains large numbers of odontoblasts (7). We also reported that proinflammatory cytokine IL-1β-induced MMP-3 activity is associated with cell proliferation of purified odontoblast-like cells derived from mouse embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) (9,10). Thus, IL-1β-induced MMP-3 appears to be pivotal in the pathophysiology of inflamed dental pulp containing rich odontoblasts.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…MMP-3 synthesis is tightly controlled in vivo (13,15). Our previous study reported that proinflammatory cytokine-induced MMP-3 actually accelerates wound healing following dental pulp injury (16)(17)(18) and promotes cell proliferation (17,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of MMP-3 is tightly controlled in vivo (12,14). Although it is intuitive that dental pulp destruction may be a function of MMPs, our previous study showed that proinflammatory cytokine-induced MMP-3 actually accelerates wound healing following dental pulp injury (15)(16)(17) and promotes cell proliferation of odontoblasts derived from mouse induced pluripotent stem (iPS) cells and embryonic stem (ES) cells (16,18,19).…”
Section: Introductionmentioning
confidence: 99%